Situation analysis of children in St. Lucia - United Nations Children’s Fund (UNICEF) (UNICEF Office for the Eastern Caribbean, 2017)
This report is the first comprehensive SitAn of children in St. Lucia focuses on the most marginalized and disadvantaged groups – children of migrant parents, those living with disabilities and those living in remote, single-parented households and poor urban communities. Due to the limitations of available quantitative data, the use of qualitative information is highlighted. The research combined an expansive desk review with over 50 national and global documents, interviews with key stakeholders (32 government and nongovernment officials) and 34 social and health workers, teachers, children, and their parents, and social workers), focus group discussions with non-governmental organizations (NGOs), and civil society and adolescents. The number of child abuse cases reported over the period of 2010-2015 totaled 1,341. Sexual abuse was the most common type of reported child abuse, accounting for 34 per cent, of all reported cases. Generally girls account for over 70 per cent of the victims. The 12-16 year old group are most often victims and many of the total cases are incest, as was the case for 29 of the 103 reports in 2014.
Keywords: marginalized children; disadvantaged groups; child abuse